2007
DOI: 10.1158/0008-5472.can-06-3026
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors α and β Are Inhibitory Modifiers of Apc-Dependent Tumorigenesis in the Proximal Colon of Min/+ Mice

Abstract: Estrogen replacement therapy in postmenopausal women is associated with a reduction in colorectal cancer risk, potentially via interactions between 17B-estradiol (E 2 ) and the estrogen receptors (ER) A and B. To study the role of E 2 in intestinal tumor inhibition, we separately crossed C57BL/ 6J-Min/+ (Min/+) mice with Era +/À and Erb +/À mice to generate ER-deficient Min/+ progeny. We found an increased incidence of visible colon tumors and dysplastic microadenomas in ER-deficient Min/+ relative to Er +/+ M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 32 publications
3
92
0
3
Order By: Relevance
“…Several studies have reported changes in ER expression as the result of treatments or changes in disease state. However, in these studies, either one of the ERs was affected or the expression of both the receptors was either increased or decreased (Cho et al 2007, Jiang et al 2008. The presented data provide new insights into the role of estrogens in the reduction of colon tumor formation in patients who suffer from colonic inflammation and suggest that an intervention can still be successful even if begun later in the tumor development process.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies have reported changes in ER expression as the result of treatments or changes in disease state. However, in these studies, either one of the ERs was affected or the expression of both the receptors was either increased or decreased (Cho et al 2007, Jiang et al 2008. The presented data provide new insights into the role of estrogens in the reduction of colon tumor formation in patients who suffer from colonic inflammation and suggest that an intervention can still be successful even if begun later in the tumor development process.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, adenocarcinomas exhibited positive protein staining for ERa and exhibited significantly increased Era mRNA expression: as high as 300-fold over the control tissues, supporting the idea that ERa activity could be increased in the colon tumors. Contrarily, studies conducted utilizing the APCmin/C mouse model of intestinal carcinogenesis suggest that the loss of ERa was detrimental to the colon (Cho et al 2007, Cleveland et al 2009). These observed disparities are probably the result of underlying differences between the APCmin/C mouse model and the inflammation protocol used here.…”
Section: Discussionmentioning
confidence: 99%
“…This estrogen effect was not reproduced in a subsequent report by the same group, however (24). In a later analysis of the effects of estrogen on colonic adenomagenesis using Er receptor mutant mice (25), OVX plus hormone replacement was not performed, and male and female mice were not differentiated. Studies in mice with intact endogenous hormone production leave open the possibility that genetically inactivating only one of the two Er receptors leads to off-target hormone action.…”
Section: Discussionmentioning
confidence: 90%
“…The genetically predisposed animal models for FAP syndrome exhibit high incidence of adenoma predominantly in the small intestine, rather than in the colon (10)(11)(12). However, genetic manipulation of the Apc mutant mouse through crosses with BubR1 +/-(17), Smad-3 (18), ER-· +/-, ER-ß +/-and ER-ß -/- (19), Fabpl-Cre/Apc-lox-p conditional truncated Apc mice (20) and Muc2 (21) has been demonstrated to specifically accelerate colon carcinogenesis. Thus, reliable colon cell culture model with Apc mutation and quantifiable carcinogenic risk should provide an alternative approach complementing the existing preclinical genetically predisposed animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Min (17), Smad-3/Apc Min (18), ER-ß/Apc Min (19), and Muc2/Apc (21) that exhibit increased incidence of colon carcinogenesis. Taken together, these aspects are expected to strengthen the concept that genetically engineered mice represent valuable predictive models for human colon carcinogenesis and chemoprevention (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%